Low thrombin generation during major orthopaedic surgery fails to predict the bleeding risk in inhibitor patients treated with bypassing agents. (16th May 2016) - Mancuso, M. E.; Chantarangkul, V.; Clerici, M.; Fasulo, M. R.; Padovan, L.; Scalambrino, E.; Peyvandi, F.; Tripodi, A.; Santagostino, E.
Abstract : Introduction: In the presence of high‐titre inhibitors, haemostatic bypassing agents are used to control bleeding and perform surgery. In this setting, no specific laboratory test is yet available to guide drug choice, monitor treatment efficacy and predict the risk of bleeding. Aim: The aims of this study, carried out in patients candidate to orthopaedic surgery, were to assess the dose‐dependent increase in thrombin generation (TG) after infusion of bypassing agents and to evaluate whether or not a correlation existed between the haemostatic efficacy of bypassing therapies and perioperative TG values. Methods and Results: TG was measured in 16 inhibitor patients, 10 of whom underwent 11 major orthopaedic procedures. In the non‐bleeding state, TG significantly improved 30 min after whichever dose ( P < 0.01), with no dose–response relationship when values obtained after different rFVIIa doses were compared. TG significantly improved 30 min after the preoperative bolus ( P < 0.05), while during the postoperative period TG values measured before and after dosing did not differ. Moreover, postoperative TG values were similar or even more impaired ( P ≤ 0.05) than those measured before preoperative dosing. No difference was found by comparing procedures with and without bleeding complications and yet no bleeding occurred in spite of persistently low TG values in one‐third of procedures. Conclusion: This study fails to support a definite role for the TG assay as a reliable laboratory tool to monitor the haemostatic efficacy of bypassing therapies and as a predictor of the risk of bleeding in inhibitor patients using these agents during orthopaedic surgery.